Nutritional Status of The Government School Children of Adolescent Age Group in Urban Areas of District Gautambudh-Nagar, Uttar Pradesh - Shalini Srivastav; Harsh Mahajan; Vijay L Grover (Medsci Publications, 2013)
Introduction: Adolescents are overlooked in most health programs as they are basically considered healthy population but the scenario varies. The present study was done with the objective of assessing the nutritional status of adolescent children attending a school in urban resettlement colony. Methodology: A cross-sectional study was done covering 392 children between 10-19 years of age from two government schools and interviewed and anthropometric measurements taken. Results: The overall prevalence of thinness was found to be 23.2% and severe thinness was found to be 7.4%.The prevalence of thinness and severe thinness in boys was 24.1% and 8.6% respectively whereas in girls it was comparatively low thinness 20.6 and 3.9%. Overall 12.5% children were found to be suffering from stunting and 1.5% from severe stunting. Moderate stunting was found in 13.7% and 12% girls whereas severe stunting was found in 0.7% boys and 3.9% girls. Conclusion: Adolescents have the lowest mortality among the different age groups and have therefore received low priority in national health programs but considering the high prevalence of malnutrition in this important transitional phase of human life, the adolescent nutrition should be given prior importance in nutritional programs.